2023
DOI: 10.1098/rspb.2022.2410
|View full text |Cite
|
Sign up to set email alerts
|

Explaining flexible continuous speech comprehension from individual motor rhythms

Abstract: When speech is too fast, the tracking of the acoustic signal along the auditory pathway deteriorates, leading to suboptimal speech segmentation and decoding of speech information. Thus, speech comprehension is limited by the temporal constraints of the auditory system. Here we ask whether individual differences in auditory-motor coupling strength in part shape these temporal constraints. In two behavioural experiments, we characterize individual differences in the comprehension of naturalistic speech as functi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 92 publications
2
9
0
Order By: Relevance
“…This finding is in line with the proposal that perception and production of rhythms are governed by a system of multiple coupled oscillators ( Zalta et al, 2020 ; Assaneo et al, 2021 ), with the observed preferred rate in any task being jointly influenced by preferred rate of a perceptual (in this case, auditory) oscillator, preferred rate of a motor oscillator, and the coupling strength between these two nodes. Indeed, similar discrepancies between preferred rates of auditory and motor oscillators were observed in speech comprehension and were attributed to individual differences in auditory-motor coupling ( Lubinus et al, 2023 ). Under this assumption, we propose that the differences between preferred rate estimates from tasks with and without tapping (motor) responses, i.e., the degree of slowing when the motor component is added, will increase with the difference in eigenfrequencies of the perceptual and motor oscillators (their detuning), and decrease with increasing coupling strength.…”
Section: Discussionmentioning
confidence: 81%
“…This finding is in line with the proposal that perception and production of rhythms are governed by a system of multiple coupled oscillators ( Zalta et al, 2020 ; Assaneo et al, 2021 ), with the observed preferred rate in any task being jointly influenced by preferred rate of a perceptual (in this case, auditory) oscillator, preferred rate of a motor oscillator, and the coupling strength between these two nodes. Indeed, similar discrepancies between preferred rates of auditory and motor oscillators were observed in speech comprehension and were attributed to individual differences in auditory-motor coupling ( Lubinus et al, 2023 ). Under this assumption, we propose that the differences between preferred rate estimates from tasks with and without tapping (motor) responses, i.e., the degree of slowing when the motor component is added, will increase with the difference in eigenfrequencies of the perceptual and motor oscillators (their detuning), and decrease with increasing coupling strength.…”
Section: Discussionmentioning
confidence: 81%
“…Interestingly, a theta-frequency-specific coupling between auditory and motor cortices has been found that matches the average syllabic rate, which has been termed "intrinsic speech-motor rhythm" ; see also: Barchet et al, o. J.;He et al, 2023). Importantly, behavioral studies have related individual intrinsic motor rhythms in the theta band (quantified by the speaking rate) and individual synchronization tendencies (mapping auditory-motor coupling strength) to speech perception skills (Assaneo et al, 2019(Assaneo et al, , 2021Lubinus et al, 2023; see also : Pfordresher et al, 2021). Notably, the relationship between endogenous motor rhythms and perception has also been behaviorally estimated and computationally modelled in the field of music research (Zamm et al, 2018;Roman et al, 2023).…”
Section: Hemispheric Lateralization Of Brain Rhythmsmentioning
confidence: 99%
“…Using phase-coupling, it has been shown that the brain engages in different states characterized by frequency-specific connectivity patterns, for example posterior alpha and anterior delta/theta (below 4 Hz and 4-8 Hz, respectively) network activity (Vidaurre et al, 2018). Overall, functional connectivity networks highlight long-range frequency-specific activity during rest, but the varied and diverse rhythmic activity of different brain areas can be more granularly captured by taking a closer look at region-specific patterns of brain activity, as captured for example by spectral profiles (Keitel & Gross, 2016;Mellem et al, 2017;Capilla et al, 2022;Komorowski et al, 2023;Lubinus et al, 2023).…”
Section: Network Of Endogenous Brain Rhythmsmentioning
confidence: 99%
“…Strikingly, temporal prediction, especially the rhythmic form, is closely related to the motor system [16][17][18]. For example, in daily life, we often observe enhanced performances in beat-based activities such as singing, playing musical instruments, and perceiving emotional changes in opera when rhythmic motion is involved [17,19,20]. This phenomenon can be explained by the dynamic attending theory [21,22], which suggests that the motor system aligns attentional fluctuations with the timing of task-relevant events.…”
Section: Introductionmentioning
confidence: 97%